Genesis of the Xifeng Low-Temperature Geothermal Field, Guizhou, SW China: Constrains From Geology, Element Geochemistry, and D-O Isotopes - Li, Yanyan; Dor, Ji; Zhang, Chengjiang; Wang, Guiling; Zhang, Baojian; Zhang, Fangfang; Xing, Yifei (Frontiers in Earth Science, 2021)
The Xifeng geothermal field is located in the Yangtze Craton, SW China, and is one of the most representative low temperature geothermal field in China. Widespread thermal anomalies, hot springs, geothermal wells have been reported by previous studies. However, the nature and forming mechanisms of the field remain poorly understood. Element geochemical (Ions, Rare Earth Elements) and stable isotopic (D, O) composition of hot springs, geothermal fluids, rivers, and cold springs from different location of the Xifeng geothermal field have been analyzed in this study. The ions studies reveal that most samples are featured with Ca-Mg-HCO3 type, excepting Xifeng hot springs, which characterized by Ca-Mg-HCO3-SO4 type. Based on quartz geothermometers, the estimated reservoir temperature is 77 ℃. The results of stable isotopes (D, O) manifest that the Xifeng geothermal system was recharged by meteoric water at elevation of 1583 m from SW to NE. The research of rare earth elements (REE) reveal that their accumulation characteristics and obvious positive Eu anomaly were inherited from host feldspar-bearing reservoir dolomites through water-rock interactions. Combined with these observations, geological setting, and previous studies, it is concluded that the formation of Xifeng geothermal field were resulted from recharge, deep circulation, and rose again of the meteoric water along the faults. First, meteoric water infiltrated to depth through faults and crack zones. Second, the deep-infiltrated water was heated up by radioactive heat, deep heat, and tectonic frictional heat. Finally, as the warmed-up waters undergoing a considerable deep circulation in the reservoir, it will be rose again along the main faults and mixed with groundwater near the surface. Taken together, we suggest that the Xifeng geothermal system should be assigned to a faults-controlling and deeply circulating meteoric water of low temperature category.